The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1111/j.1476-5381.1993.tb13638.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous tachykinins facilitate transmission through parasympathetic ganglia in guinea‐pig trachea

Abstract: 1 Exogenous and endogenous tachykinins facilitate cholinergic nerve-induced bronchoconstriction in guinea-pig. Using a vagally innervated guinea-pig tracheal tube preparation we have investigated the involvement of endogenous capsaicin-sensitive neuropeptides in both pre-and postganglionic cholinergic neurotransmission. The effects of the neutral endopeptidase inhibitor (NEP), phosphoramidon, were investigated in this preparation either alone or in conjunction with sensory neuropeptide depletion by capsaicin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 28 publications
(54 reference statements)
3
33
2
Order By: Relevance
“…Thus the logical explanation of the IL-1␤ effect is that SP alters cholinergic responsiveness. Previous studies have shown that SP enhances cholinergic responsiveness either through a direct effect on airway smooth muscle (49) or by enhancing ACh release from parasympathetic nerve terminals (40,44,52). The data in the present study do not discriminate between these two mechanisms because cholinergic responsiveness was enhanced both by cholinergic agonists and by EFS.…”
Section: Discussionmentioning
confidence: 27%
“…Thus the logical explanation of the IL-1␤ effect is that SP alters cholinergic responsiveness. Previous studies have shown that SP enhances cholinergic responsiveness either through a direct effect on airway smooth muscle (49) or by enhancing ACh release from parasympathetic nerve terminals (40,44,52). The data in the present study do not discriminate between these two mechanisms because cholinergic responsiveness was enhanced both by cholinergic agonists and by EFS.…”
Section: Discussionmentioning
confidence: 27%
“…However, in rabbit trachea the tachykinin receptors mediating this effect were not investigated. Exogenous tachykinins also potentiate cholinergic neurotransmission at pre-and postganglionic nerve terminals in guinea-pig trachea (Hall et al, 1989;Watson et al, 1993). The tachykinin receptor mediating these effects appeared to be of the NK, receptor subtype (Watson et al, 1993).…”
Section: Discussionmentioning
confidence: 91%
“…Exogenous tachykinins also potentiate cholinergic neurotransmission at pre-and postganglionic nerve terminals in guinea-pig trachea (Hall et al, 1989;Watson et al, 1993). The tachykinin receptor mediating these effects appeared to be of the NK, receptor subtype (Watson et al, 1993). However, in addition, NKA, which preferentially stimulates NK2 receptors facilitated contractions evoked by pre-and postganglionic nerve stimulation (Hall et al, 1989;Watson et al, 1993).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations